Predicting Alzheimer's Disease: Neuropsychological Tests, Self Reports, and Informant Reports of Cognitive Difficulties - Rabin, Laura A. (2012)
BACKGROUND/OBJECTIVES: Despite the strong need for evidence-based diagnostics, there is disagreement about the cognitive tools that best predict incident Alzheimer's disease (AD) in nondemented elders. We investigated the independent and combined contributions to the risk of AD of three key domains of cognitive assessment: neuropsychological measurement, self reports, and informant reports. DESIGN: Longitudinal, community-based sample. SETTING: Einstein Aging Study. PARTICIPANTS: Six hundred twenty-seven non-demented older adults aged 70 and above systematically recruited from the Bronx, NY. MEASUREMENTS: Comprehensive assessment included neurological exam, behavioral questions, and neuropsychological testing. AD diagnoses were based on DSM-IV criteria assigned at a multidisciplinary consensus case conference. The major statistical analyses utilized Cox proportional hazards models (with age as the time scale), adjusted for gender, education, and depressive symptoms. RESULTS: Forty-eight participants developed incident AD during a median of 3.3 years of follow-up. Self and informant reports of cognitive status as well as baseline scores on tests of episodic memory and psychomotor speed predicted the onset of AD. In models examining all the variables simultaneously, however, only the episodic memory tests and informant reports were associated with risk of AD. A likelihood ratio test confirmed the incremental effect of informant reports in addition to the neuropsychological test scores (P=0.035). CONCLUSION: Informant ratings improved the prediction of AD conversion above and beyond objective memory impairment in non-demented elders. Combining these cognitive measures may provide a useful, empirical method for identifying individuals at high risk for future AD.